2012
DOI: 10.1016/s0968-8080(12)40679-6
|View full text |Cite
|
Sign up to set email alerts
|

Measuring improvements in sexual and reproductive health and rights in sub-Saharan Africa

Abstract: Recent studies on development aid from European donors revealed that their funding of the health sector in sub-Saharan Africa rarely includes performance measures suitable for tracking operational progress in improving sexual and reproductive health and rights. Analysis of health sector agreements verifies this. Particularly lacking are metrics related to four critically important areas: 1) reducing mortality and morbidity from unsafe abortion, 2) preventing and treating gender-based violence, 3) reducing unwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Our list also includes examples of country level indicators that can measure the performance of health sector programmes in ensuring sexual and reproductive health, including for abortion services. 11 We have conducted this review as the first step in a multi-stage process for deriving a set of standardised indicators which can be used across reproductive health programmes in diverse settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our list also includes examples of country level indicators that can measure the performance of health sector programmes in ensuring sexual and reproductive health, including for abortion services. 11 We have conducted this review as the first step in a multi-stage process for deriving a set of standardised indicators which can be used across reproductive health programmes in diverse settings.…”
Section: Discussionmentioning
confidence: 99%
“…These results also aim to inform a future research agenda on abortion indicators measurement. While our list of indicators is extensive, there remains a need in some areas to develop or test new indicators: for example, to broaden the type of health outcome indicators for abortion to quality of life and functioning; to respond to the challenge of collecting valid data in the community as the provision of abortion care is shifting to community-based distribution of medical abortion; to standardise indicators, in particular those that are morbidity related 29 ; to measure performance of the health sector 11 and to align with other initiatives on effective coverage 30 and health system strengthening monitoring. 31 Comprehensive measurement of patient-centred indicators, such as women's experience of care is also required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This aspect is of focus in that it is particularly important to adolescent health [7], [8]. It is indispensable to their growth and the impact of such knowledge will greatly influence their lives as they proceed into adulthood [9]- [11].…”
Section: Introductionmentioning
confidence: 99%
“…Existing indicators for abortion care quality are poorly defined, inconsistently used, incomplete, and no consensus has been formed around their relevance within quality frameworks. 3 , 4 , 5 Furthermore, existing measures do not fully address client-centred elements of quality and are not applicable to increasingly common out-of-facility administration of medication abortion (MA). A 2017 systematic review by Dennis, Blanchard and Bessenaar found 75 unique indicators used to measure abortion care quality with varying application.…”
Section: Introductionmentioning
confidence: 99%